Knowledge and abuse of psychoactive substances among commercial drivers in Ibadan, Oyo State, Nigeria (2018)
This study examined knowledge and abuse of psychoactive substances among commercial drivers in Ibadan, Oyo State, Nigeria. A descriptive survey design was used for this study. One hundred commercial drivers were sampled from commercial motor parks in Ibadan. The instrument used for the study was a self-developed questionnaire which was appropriately validated by experts and cronbach alpha was used to establish the reliability. Two research questions were raised to guide the study. Data were analysed using descriptive statistics of mean and standard deviation. Results showed that commercial drivers in Ibadan do not have knowledge of psychoactive substance and they indulge in abuse of psychoactive substances. It was therefore recommended that drug education with greater emphasis on negative effects of psychoactive substances should be organized regularly for commercial drivers in Ibadan metropolis.